Emerging technologies and new business models: A review on disruptive business models - Giovana Sordi Schiavi; Ariel Behr (Innovation & Management Review, 2018)
Purpose: This paper aims to conduct a review on disruptive business models. Considering that competition among companies will not only happen through new products, services or technologies but also through innovative business models, the disruptive business models arise to replace the existing business models, adapting the organizational structures to the products and services offered and emphasizing the proposition of unique value. Design/methodology/approach: The literature on this topic was revised, allowing the obtaining of the state of the art and the construction of a research agenda. The analyzed literature was obtained from systematic searches by the term disruptive business model in some databases. For the analysis of the data, the content analysis strategy was used through categorizations in the material exploration phase, and, later, for the processing of the results, the authors made use of inference and interpretation regarding the content analyzed. Findings: The collected literature made it possible to obtain a set of data formed by different views of authors on disruptive business models, which was analyzed and categorized to make new inferences and interpretations. Originality/value: Considering that the literature on the disruptive process of business models is emerging and addressing an important phenomenon in the market that lacks the theoretical basis to sustain it, this paper contributes by presenting a consolidated examination on this subject, thus deepening the theoretical analyzes on this topic and reducing this lack in the literature. This study also presents a research agenda, which clarifies the disruptive business model gap and reveals some opportunities for future empirical researches.
Keywords: 650; Innovation; Business models; Emerging technologies; Disruptive business models